Bentuk dan Kendala Penerapan Pembelajaran Partisipatif di Sekolah Tinggi Agama Islam Negeri (STAIN) Jember: Forms and Challenges in Implementing Participatory Learning at the State Islamic College (STAIN) Jember - Mundir Mundir (Fenomena, 2006)
The shift toward competency-based curricula in Indonesian higher education necessitates participative learning approaches, yet their implementation often faces multidimensional obstacles. This study aims to describe the forms and constraints of participative learning implementation at STAIN Jember. Using a qualitative descriptive approach with an emic perspective, data were collected through observation, questionnaires, focus group discussions, in-depth interviews, and documentation from lecturers and students. The findings reveal that participative learning is implemented through stages of rapport building, needs identification, objective formulation, program planning, and active learning strategies such as group discussions, presentations, jigsaw, and card sort, with limited student involvement in assessment. Key constraints include human factors (unprepared classrooms, passive participation), unclear learning objectives, limited reference materials, unfavorable class schedules, and inadequate facilities such as OHP and electricity. However, active and varied strategies, supported by internet access, can mitigate these constraints. The study concludes that participative learning is viable but requires institutional support to address logistical and attitudinal barriers, and recommends enhanced training and facility provision. Pergeseran menuju kurikulum berbasis kompetensi di pendidikan tinggi Indonesia menuntut pendekatan pembelajaran partisipatif, namun implementasinya sering menghadapi kendala multidimensi. Penelitian ini bertujuan mendeskripsikan bentuk dan kendala penerapan pembelajaran partisipatif di STAIN Jember. Dengan pendekatan kualitatif deskriptif perspektif emik, data dikumpulkan melalui observasi, angket, diskusi kelompok terfokus, wawancara mendalam, dan dokumentasi dari dosen dan mahasiswa. Temuan menunjukkan pembelajaran partisipatif diterapkan melalui tahap pembinaan keakraban, identifikasi kebutuhan, perumusan tujuan, penyusunan program, strategi aktif seperti diskusi kelompok, presentasi, jigsaw, dan card sort, serta keterlibatan mahasiswa yang terbatas dalam penilaian. Kendala utama meliputi faktor manusia (kelas tidak siap, partisipasi semu), tujuan tidak jelas, terbatasnya bahan ajar, jadwal tidak ideal, dan fasilitas seperti OHP dan listrik. Namun, strategi aktif dan variatif serta dukungan internet dapat mengurangi kendala tersebut. Penelitian menyimpulkan pembelajaran partisipatif layak diterapkan dengan dukungan kelembagaan untuk mengatasi hambatan logistik dan sikap, serta merekomendasikan peningkatan pelatihan dan fasilitas.